INTERACTIVE TECHNOLOGIES IN THE DEVELOPMENT OF STUDENTS' CREATIVE ACTIVITY BASED ON AN INTEGRATIVE APPROACH (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the role of interactive technologies in enhancing students’ creative activity within the framework of an integrative approach. Modern education requires not only the acquisition of knowledge but also the development of creativity, problem-solving abilities, and innovative thinking. The effective use of interactive technologies, such as digital platforms, multimedia tools, simulation models, and collaborative applications, opens new opportunities for fostering creativity. An integrative approach allows the combination of different subjects, skills, and competencies into a unified educational process, thereby reinforcing students’ motivation and engagement.